Temporomandibular disorders: Old ideas and new concepts. (June 2017) - List, Thomas; Jensen, Rigmor Højland
Background: Temporomandibular disorders (TMD) is an umbrella term for pain and dysfunction involving the masticatory muscles and the temporomandibular joints (TMJs). TMD is the most common orofacial pain condition. Its prominent features include regional pain in the face and preauricular area, limitations in jaw movement, and noise from the TMJs during jaw movements. TMD affects up to 15% of adults and 7% of adolescents. Chronic pain is the overwhelming reason that patients with TMD seek treatment. TMD can associate with impaired general health, depression, and other psychological disabilities, and may affect the quality of life of the patient. Assessment: Evaluations indicate that the recently published Diagnostic Criteria for TMD (DC/TMD) are reliable and valid. These criteria cover the most common types of TMD, which include pain-related disorders (e.g., myalgia, headache attributable to TMD, and arthralgia) as well as disorders associated with the TMJ (primarily disc displacements and degenerative disease). As peripheral mechanisms most likely play a role in the onset of TMD, a detailed muscle examination is recommended. The persistence of pain involves more central factors, such as sensitization of the supraspinal neurons and second-order neurons at the level of the spinal dorsal horn/trigeminal nucleus, imbalanced antinociceptive activity, and strong genetic predisposition, which also is included in DC/TMD. Conclusion: The etiology is complex and still not clearly understood, but several biological and psychosocial risk factors for TMD have been identified. Several studies indicate that patients with TMD improve with a combination of noninvasive therapies, including behavior therapy, pharmacotherapy, physical therapy, and occlusal appliances. More stringently designed studies, however, are needed to assess treatment efficacy and how to tailor treatment to the individual patient.